2014
DOI: 10.1371/journal.pone.0095775
|View full text |Cite|
|
Sign up to set email alerts
|

The Elemental Composition of Demospongiae from the Red Sea, Gulf of Aqaba

Abstract: Trace elements are vital for the growth and development of all organisms. Little is known about the elemental content and trace metal biology of Red Sea demosponges. This study establishes an initial database of sponge elemental content. It provides the necessary foundation for further research of the mechanisms used by sponges to regulate the uptake, accumulation, and storage of metals. The metal content of 16 common sponge species was determined using ICP measurements. A combination of statistical methods wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 58 publications
3
29
1
Order By: Relevance
“…These results were higher than those reported in the present study for Cd and Cu, lower for Ag and overall comparable for Zn and As. Mayzel et al (2014) analyzed 16 sponge species and reported BCF consistently lower than 1 for Ba (except for one specie) and V; additionally, the study shows BCF > 1 for As, Cd and Zn. A significant As BCF of 477 was previously measured in only one sponge specie, Theonella swinhoei, which was explained by the presence of a particular bacterium (Mayzel et al, 2014).…”
Section: Concentrations Inmentioning
confidence: 87%
See 3 more Smart Citations
“…These results were higher than those reported in the present study for Cd and Cu, lower for Ag and overall comparable for Zn and As. Mayzel et al (2014) analyzed 16 sponge species and reported BCF consistently lower than 1 for Ba (except for one specie) and V; additionally, the study shows BCF > 1 for As, Cd and Zn. A significant As BCF of 477 was previously measured in only one sponge specie, Theonella swinhoei, which was explained by the presence of a particular bacterium (Mayzel et al, 2014).…”
Section: Concentrations Inmentioning
confidence: 87%
“…BCF obtained for V, Pb, Ba and Ni were lower than 1 (or close) regardless of the sponge species, leading to the conclusion that these elements are more accumulated in sediments than in sponge' tissue. Ba was demonstrated to be toxic for some sponges (Ostrom and Simpson, 1978;Tompkins-MacDonald et al, 2009), and its BCF were already reported lower than 1 in several sponges species (Mayzel et al, 2014), thus implying its non-essential role in sponges' biological activities. In the same manner, a similar assumption can be made for V, which showed the same behavior in other sponge species, as reported by Mayzel et al (2014).…”
Section: Bio-concentration Factors (Bcf)mentioning
confidence: 98%
See 2 more Smart Citations
“…On hard substrata, sponges are one of the top spatial competitors (Bell, 2008) and have recently been proposed as model organisms to monitor aquatic contamination, in addition to the already existing and well known "Mussel Watch Program" (Genta-Jouve et al, 2012). The bioaccumulation of trace elements in sponges was suggested to differ according to sponge species and the element of interest (Batista et al, 2014;Mayzel et al, 2014;Patel et al, 1985). Only few studies focused on As bioaccumulation in sponges (Aly et al, 2013;Araújo et al, 2003;Batista et al, 2014;Denton et al, 2006;Keren et al, 2015;Keren et al, 2016;Keren et al, 2017;Padovan et al, 2012;Pan et al, 2011;Perez et al, 2005;Schaeffer et al, 2006;Shiomi et al, 1988;Vaskovsky et al, 1972;Venkateswara Rao et al, 2009;Yamaoka et al, 2001;Yamaoka et al, 2006).…”
Section: Introductionmentioning
confidence: 99%